Theoretical and experimental investigation of the role of viscosity and surface tension in dropwise evaporation at very high substrate temperature. (March 2019) - Mohapatra, S.S.; Pradhan, Suryakant; Pati, A.R.; Barik, K.
Highlights: Critical droplet diameter for significant absorption of heat is found to be 1.5 mm. Decreasing viscosity and surface tension favors heat transfer rate. Late recoiling and high spreading leads to dropwise evaporation enhancement. The lowest residence favors high renewal rate but less heat extraction rate. Abstract: Cooling techniques such as spray and air-atomized spray cooling are based on the basic phenomenon i.e. dropwise evaporative cooling. The dropwise evaporative cooling mechanism is mainly controlled by the thermo-physical properties such as surface tension, viscosity and specific heat and process parameter such as substrate temperature and the process variables defining droplet dynamics during evaporation. In the current work, an attempt has been made to reveal the heat transfer mechanism at substrate temperature around 600 °C for the successful implementation in industry. Various coolants such as tween-20, ethanol, and acetone were selected to identify the behaviour of surface tension and viscosity. The decreasing surface tension and viscosity (Tween-20) promotes evaporation during spreading and recoiling characteristic; however, this is not observed in case of pure water. The decreasing surface tension and increasing viscosity (ethanol) creates early recoiling and strong dancing characteristic due to the thermal kick and buoyancy effect. These effects are the minimum in case of acetone added water depicting significant reduction in surface tension and viscosity. Moreover, the critical diameter (1.5 mm) and minimum residence time (170 ms) to get enhancement are also determined from the experiment and the model result corroborates the aforesaid.